2010
DOI: 10.3109/01902140903575989
|View full text |Cite
|
Sign up to set email alerts
|

MCP1 −2518Polymorphism and chronic obstructive pulmonary disease in Taiwanese men

Abstract: Monocyte chemoattractant protein-1 (MCP-1) plays a major role in the recruitment of inflammatory cells to the lungs of patients with chronic obstructive pulmonary disease (COPD). However, the influence of MCP1 gene polymorphism on COPD development has not been studied. This study aimed to investigate the association between MCP1 -2518 polymorphisms and COPD and between this polymorphism and plasma MCP-1 levels. The plasma MCP-1 was measured by using an enzyme-linked immunosorbent assay and polymorphisms detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Smoking induces a significant increase of monocyte chemotactic protein (MCP)-1 levels in the bronchoalveolar lavage (BAL) fluid of both healthy smokers 3 and patients with chronic bronchitis, 4 and COPD patients show higher plasma MCP-1 levels compared with healthy controls. 5 However, MCP-1 plasma levels have not been analyzed according to the different COPD phenotypes. Both interleukin (IL)-1α and IL-1β are proinflammatory cytokines produced mainly by monocytes, macrophages, and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking induces a significant increase of monocyte chemotactic protein (MCP)-1 levels in the bronchoalveolar lavage (BAL) fluid of both healthy smokers 3 and patients with chronic bronchitis, 4 and COPD patients show higher plasma MCP-1 levels compared with healthy controls. 5 However, MCP-1 plasma levels have not been analyzed according to the different COPD phenotypes. Both interleukin (IL)-1α and IL-1β are proinflammatory cytokines produced mainly by monocytes, macrophages, and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, it is stated that MCP-1 -2518 A/G and CCR2 190 G/A gene polymorphisms may be effective in COPD formation (12). Liu et al found no association between MCP1 -2518 gene polymorphism and COPD and this gene polymorphism and plasma MCP-1 levels in the Taiwanese men (26).…”
Section: Discussionmentioning
confidence: 99%
“…MCP‐1 levels are increased in the sputum, BALF, and lungs of patients with COPD, and MCP‐1 is also expressed in macrophages, T‐cells, endothelial cells, and bronchial epithelial cells of human lung [de Boer et al, ; Traves et al, ]. In smokers with COPD, expression of MCP‐1 is elevated as compared to non‐COPD smokers and acts as a potent chemoattractant for neutrophils and monocytes [Liu et al, ; Blidberg et al, ]. MCP‐1 and MIP‐1a are validated markers for chronic inflammation in COPD patients and consequently compounds that inhibit neutrophil influx and chemokine expression may be effective in attenuating COPD progression.…”
Section: Discussionmentioning
confidence: 99%